The relationship between selected anthropometric characteristics and technique parameters in breaststroke swimming - Pacheco, Jocelyn J. (College of Human Kinetics, University of the Philippines Diliman, 2003)
The aim of this study was to determine the relationships between selected anthropometric characteristics and technique parameters in breastroke swimming. Specifically, the study determined which anthropometric characteristics significantly influence swimmers' stroke length, stroke frequency and velocity. This high school swimmers of varied training levels from four different swim clubs in Iloilo were measured for stature, sitting height and arm span. Swimming velocity, stroke length, and stroke frequency were computed from a 50m-swim test.Using SPSS descriptive statistics of stature, sitting height, arm span, stroke length, stroke frequency and velocity were derived. Pearson Product Moment Correlation was used to find the relationship on three anthropometric characteristics and three stroke technique parameters. Results of the study revealed that at the average Filipino adolescents (152.2 cm); possess longer arm span (159.763 cm) and higher sitting height/stature ratio (52.54%). There were significant positive relationships on all anthropometric measurements, between SL and V and between SL and arm span. However, there was a significant negative relationship between SL and SF. Furthermore, there was no significant relationship found between SF and V, stature and V, sitting height and V and arm span and V. Therefore, for hypotheses 1 breaststroke swimming, the hypothesis is rejected only when the following variables are considered: stroke length and stroke frequency, velocity and stroke length. The hypothesis is, however, accepted when the variables stroke frequency and velocity are considered. Hypothesis 2 which states that "there is no significant relationship among the three (3) anthropometric characteristics of breaststroke swimmers: stature and sitting height, sitting height and arm span, arm span and stature" is rejected. With hypothesis 3 which states that "There is no significant relationship between the three (3) anthropometric characteristics of breaststroke swimmers and the three (3) technique parameters in breaststroke swimming.", the hypothesis is rejected only when the variables arm span and stroke length are considered. This study may provide a useful starting point in predicting some future potential of individuals specifically in swimming talent identification. Further investigation on anthropometric characteristics such as weight, body circumferences, upper and lower leg length, and length and breadth of feet of the swimmers in different swimming strokes-freestyle, breaststroke, backstroke and butterfly-must be undertaken . It is further suggested that more researches on the same age group and/ or varied groups and different levels of competition with bigger population be carried out because it increases the accuracy of the results of the measurements made. Accurate results lead to a reliable representation of the population of a research project. Swimming at 80% effort is of significance in the middle distance events. To embark on more experiments on the 100% best time (spirit pace) of swimmers are likewise proposed.